On some expansions of the multidimensional symmetric stable densities - Kalinauskaitė, N. (Lithuanian Mathematical Journal, 1970)
The abstracts (in two languages) can be found in the pdf file of the article. Original author name(s) and title in Russian and Lithuanian: Н. Калинаускайте. Некоторые разложения многомерных симметрических устойчивых плотностей N. Kalinauskaitė. Kai kurie daugiamačių simetrinių stabilių tankių išdėstymai eilute